My Country My Life - Advani, L. K. (New Delhi, India Rupa & Co., 2008)
Memoirs of a former deputy prime minister of India and opposition leader in Lok Sabha of Bharatiya Janata Party, political party in India.
Include Insex, Appendix, References, Glossary and Colour Illustration
Keywords: Politicians -- India -- Bharatiya Janata Party